A new method of measuring shoulder hand behind back movement: Reliability, values in symptomatic and asymptomatic people, effect of hand dominance, and side-to-side variability. (2nd October 2016) - Satpute, Kiran; Hall, Toby; Kumar, Senthil; Deodhar, Ankeeta
ABSTRACT: Shoulder hand behind back (HBB) range of motion (ROM) is a useful measure of impairment and treatment outcome. The purpose of this repeated measures study was to identify inter- and intra-rater reliability, of a new simplified method of measuring HBB ROM. Two experienced raters measured HBB ROM with a bubble inclinometer on 25 people (aged 42–75 years, 14 female) with unilateral shoulder dysfunction and 25 age- and gender-matched asymptomatic subjects on two different occasions. Statistical analysis included calculation of intra-class correlation coefficients (ICCs), minimal detectable change (MDC), standard error of measurement (SEM), Pearson correlation coefficient ( r ), coefficient of determination ( R 2 ), and the lower bound score. Mean HBB ROM was 108.6° (SD = 16.3) and 23.9° (SD = 10.5) on the pain-free and symptomatic side, respectively. Both intra-rater and inter-rater reliability were high (ICC > 0.80). For asymptomatic people the SEM was at most 3° and MDC was 8° with a strong correlation between the dominant and nondominant sides ( r > 0.72). The mean absolute values and lower bound scores were at most 10.2° and 26.0°, respectively. These results indicate that this new and novel method of measuring HBB ROM is accurate, has good inter- and intra-rater reliability, and provides normal values for between-limb ROM variability.